Initial Rotation Characteristic Investigation of a Hybrid Savonius - Darrieus Wind Turbine using 6 DOF Computational Fluid Dynamics - Hangga Wicaksono; Sugeng Hadi Susilo; Bayu Pranoto; Muhammad Fakhruddin (Universitas Sebelas Maret, 2021)
The inconsistency of the wind flow considered as one of the factors which tend to decrease the performance of the wind turbine. This paper proposes a further analysis of the initial rotation characteristic of a hybrid Savonius-Darrieus wind turbine. The addition of the Darrieus blade intends to increase the aerodynamic stability of the overlapping Savonius turbine. This study implements 2D Computational Fluid Dynamics (CFD) transient analysis using the six Degrees of Freedom (DOF) methods in 0°, 30°, 60°, and 90° Darrieus blade position along with 2, 4, and 6 m/s wind speed variations. The results of the aerodynamic analysis show that the location of the Darrieus 30° turbine provides the greatest initial repulsion, especially when the turbine rotation is above 90°, the position of the Darrieus blade can provide additional impulse force when the Savonius turbine tends to be passive. This effect occurs more significant at higher wind speeds. Savonius with 3-blade modification has a more stable level of force distribution than the 2-blade modification, although the value is smaller. This shows that the 3-blade Savonius provide a higher stability of angular velocity development.